Níveis plasmáticos de nitrito/nitrato, GMPc e cortisol em mulheres normotensas e hipertensas após a menopausa: efeito crônico do exercício físico e exposição aguda à L-arginina - Novais, Iane de Paiva [UNESP] (2015)
After menopause, women start to present an increased prevalence of arterial hypertension. Although the mechanisms have not been completely elucidated, evidences from experimental models have attributed an increased risk of developing cardiovascular disease in this stage to decreased estrogen levels associated with oxidative stress and endothelial dysfunction. It is well stablished that physical exercise may promote beneficial effects on the cardiovascular system, acting on the nitric oxide (NO) pathway, which is a potent vasodilator released by the endothelium and regarded as essential to blood pressure (BP) control. The NO synthesis results from L-arginine substrate and several studies have demonstrated the administration of this amino acid may increase vascular function. However, the association of L-arginine and physical exercise has not been proved to potentialize the benefits provided by these elements isolatedly, especially on women presenting increased cardiovascular risk. Thus, this study aimed to investigate the chronic and acute effects of aerobic physical exercise and of acute L-arginine administration on the cardiovascular responses and endocrine-metabolic biomarkers in normotensive (NT) and hypertensive (HT) postmenopausal women as well. For this, the collected data were presented in two different moments, named Study 1 and Study 2. The objective of Study 1 was to evaluate the aerobic physical training (APT) effects on anthropometric, cardiovascular and hormonal/biochemical parameters in NT and HT postmenopausal women. Sixty-one postmenopausal women were enrolled - 33 NT and 28 HT. Anthropometric, cardiovascular and physical capacity were performed, as well as fasting blood assay to lipid profile, glycemia, NO/cGMP pathway, steroid hormones (cortisol and testosterone) and biomarkers of oxidative stress (dismutase superoxide, catalase and malondialdehyde). Posteriorly, all the participants were submitted to 8 weeks of APT ...